2016
DOI: 10.1016/j.addr.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

“Eat me” imaging and therapy

Abstract: Clearance of apoptotic debris is a vital role of the innate immune system. Drawing upon principles of apoptotic clearance, convenient delivery vehicles including intrinsic anti-inflammatory characteristics and specificity to immune cells can be engineered to aid in drug delivery. In this article, we examine the use of phosphatidylserine (PtdSer), the well-known “eat-me” signal, in nanoparticle-based therapeutics making them highly desirable “meals” for phagocytic immune cells. Use of PtdSer facilitates engulfm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 132 publications
0
37
0
Order By: Relevance
“…It should be noted that different PS receptors on different immune cells (not only APCs), upon PS ligation, will manifest different functions, including, particularly, the anti-inflammatory and even tolerogenic effects. These effects, on one hand, are in good accommodation to PS role in inducing rapid phagocytic clearance of dying cells in silence to avoid autoimmunity, but, on the other hand, count obviously against establishing the anti-pathogen immunity [93,94].…”
Section: Surface Propertymentioning
confidence: 99%
“…It should be noted that different PS receptors on different immune cells (not only APCs), upon PS ligation, will manifest different functions, including, particularly, the anti-inflammatory and even tolerogenic effects. These effects, on one hand, are in good accommodation to PS role in inducing rapid phagocytic clearance of dying cells in silence to avoid autoimmunity, but, on the other hand, count obviously against establishing the anti-pathogen immunity [93,94].…”
Section: Surface Propertymentioning
confidence: 99%
“…Recently, several studies have shown that synthetic ACs, as examples of non-cell-based therapies, might be used to enhance efferocytosis. An example of such synthetic ACs are the PtdSer-decorated nanoparticles which mimic ACs [171,172]. Hosseini et al showed in apoE-KO mice that PtdSer liposomes, which mimic ACs, effectively reduce atherosclerotic lesions by inducing poly-reactive IgM producing B1a lymphocytes [173].…”
Section: Therapeutic Aspectsmentioning
confidence: 99%
“…The incorporation of TRITC-DHPE-labeled PSLs into cells was assessed using fluorescence microscopy. The cell membranes were stained with 250 nM 3,3 0 -dioctadecyloxacarbocyanine perchlorate (DiOC18 [3]) (Invitrogen, Carlsbad, CA) for 20 min prior to PSL treatment. DiOC18(3)-stained cells were incubated with TRITC-DHPE-labeled PSLs for 3 h. Two-channel fluorescence images were obtained using a confocal laser scanning microscope (LSM 700, Carl Zeiss, Germany) at a magnification of 4003.…”
Section: Live Cell Imagingmentioning
confidence: 99%